Optimizing of parameters for the Fe-HUMIC acid complex formation using cyclic voltammetry. - Bautista, Coleen M. (2019.)
Humic acid extracted from an artesian well located at Sta. Barbara, Iloilo was used to generate a Fe-HA complex as a potential additive to bio floc systems to augment the essential mineral Fe. The humic acid obtained was black in color and had a powdery texture after oven-drying. The Fe-HA complex were prepared using 〖Fe〗^(3+) ions at different pH values specifically at pH 8, 9, and 10. Formation of the complex was investigated using the cyclic voltammetry to determine the ideal conditions to maximize the binding of the metal ion. The results showed that there are two oxidation and reduction cycles which suggests that there are two species undergoing oxidation and reduction. It is possible that the free iron and the Fe in the complex are undergoing a redox cycle although the quinone group in the humic acid can also act as redox center. Atomic Absorption Spectroscopy can help corroborate the amount of complex formed to help deduce the redox active center.
Thesis (Undergraduate, Bachelor of Arts in Chemsitry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Cyclic voltammetry